Signaling in Auctions among Competitors - Benedikt von Scarpatetti; Cédric Wasser (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
We consider a model of oligopolistic firms that have private information about their cost structure. Prior to competing in the market a competitive advantage, i.e., a cost reducing technology, is allocated to a subset of the firms by means of a multi-object auction. After the auction either all bids or only the prices to be paid are revealed to all firms. This provides an opportunity for signaling. Whether there exists an equilibrium in which bids perfectly identify the bidders' costs generally depends on the type and fierceness of the market competition, the specific auction format, and the bid announcement policy.
urn:nbn:de:bvb:19-epub-13261-9
Keywords: D44; L13; D43; D82; C72; 330; Auction; Oligopoly; Signaling; Auktionstheorie; Signalling; Wettbewerb; Theorie